John Henry Newman and the imagination - Dive, Bernard (T&T Clark, 2020)
Personal visions: the 1830s -- Faith, practical perception, and phronesis -- A work to do in England -- The impression of Christ -- The pursuit of truth -- The virtue of faith and the virtues of civilization: the 1840s and 1850s -- The virtue of faith -- Faith and civilization -- Real visions: the 1860s and 1870s -- The imagination and the metropolitan intellect -- Ex Umbris Et Imaginibus In Veritatem